2022
DOI: 10.1093/labmed/lmac113
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Evaluation of Recombinant Expression of HCV Transmembrane Protein (p7) and Detection of Anti-p7 Antibody in Serum of HCV-Infected Patients by Chemiluminescence

Abstract: Objective Our aim was to establish a chemiluminescence method for detecting anti-transmembrane protein (p7) antibody in the serum of patients with hepatitis C virus (HCV) infection. Methods The p7 gene was amplified by polymerase chain reaction using the plasmid PUC-p7 containing the p7 nucleic acid sequence of the HCV 1b genotype as the template, and recombinant plasmid pGEX-KG-p7 was constructed. After p7 fusion, the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, the study of envelope glycoproteins E1 and E2 in the serum of HCV‐infected patients is subject to some limitations, and the main difficulties of the study are as follows: there are no available kits for the detection of antibodies to E1 and E2 proteins; the existing commercial kits are mostly for the combined detection of antibodies to multiple proteins (in order to improve the detection rate of HCV infection); the inability to complete the detection of anti‐E1 and anti‐E2 individual antibodies and the small fragments of E1 and E2 proteins, which are difficult to express and purify, 11 ; and the difficulty of preparing detection kits. Therefore, in order to understand the humoral immune response of HCV envelope glycoproteins (E1, E2) in the host, this paper developed a chemiluminescence detection kit for anti‐E1 and anti‐E2 antibodies in HCV‐infected sera based on the development of kits for detecting anti‐P7 and anti‐NS2 antibodies, 12 , 13 and 45 cases of HCV‐infected sera were tested and 16 cases of anti‐E1 and 20 cases of anti‐E2 antibodies were detected, respectively. The results indicated that a certain percentage of anti‐E1 and anti‐E2 antibodies existed in HCV‐infected patients, suggesting the existence of an immune response to the HCV envelope protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of envelope glycoproteins E1 and E2 in the serum of HCV‐infected patients is subject to some limitations, and the main difficulties of the study are as follows: there are no available kits for the detection of antibodies to E1 and E2 proteins; the existing commercial kits are mostly for the combined detection of antibodies to multiple proteins (in order to improve the detection rate of HCV infection); the inability to complete the detection of anti‐E1 and anti‐E2 individual antibodies and the small fragments of E1 and E2 proteins, which are difficult to express and purify, 11 ; and the difficulty of preparing detection kits. Therefore, in order to understand the humoral immune response of HCV envelope glycoproteins (E1, E2) in the host, this paper developed a chemiluminescence detection kit for anti‐E1 and anti‐E2 antibodies in HCV‐infected sera based on the development of kits for detecting anti‐P7 and anti‐NS2 antibodies, 12 , 13 and 45 cases of HCV‐infected sera were tested and 16 cases of anti‐E1 and 20 cases of anti‐E2 antibodies were detected, respectively. The results indicated that a certain percentage of anti‐E1 and anti‐E2 antibodies existed in HCV‐infected patients, suggesting the existence of an immune response to the HCV envelope protein.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, seeking efficient and cost-effective HCV diagnostics have been actively pursued in myriad studies that highlighted the clinical utility of recombinant antigens, either as full-length or pre-selected mono-/multiple epitope(s)-based peptides [13][14][15]. In this domain, Escherichia coli-based system is the most widely used for the overexpression of recombinant antigens, given its high growth rate, relatively cheap growth media, and the high yield of recombinant proteins synthesized [16].…”
Section: Introductionmentioning
confidence: 99%